2021
DOI: 10.1139/cjc-2021-0139
|View full text |Cite
|
Sign up to set email alerts
|

Phenothiazines as dual inhibitors of SARS-CoV-2 main protease and COVID-19 inflammation

Abstract: COVID-19, caused by the severe acute respiratory coronavirus 2 (SARS-CoV-2) currently has no treatment for acute infection. The main protease (Mpro) of SARS-CoV-2 is an essential enzyme for viral replication and an attractive target for disease intervention. The phenothiazine moiety has demonstrated drug versatility for biological systems, including inhibition of butyrylcholinesterase, a property important in the cholinesterase anti-inflammatory cascade. Nineteen phenothiazine drugs were investigated using in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Thus, further research is warranted to evaluate more detailed mechanisms of phenothiazines to inhibit the entry of SARS-CoV-2 besides inhibiting CTSL cleavage. Theoretically, phenothiazines as a class of compounds seem not that specific as they were also reported to bind numerous other molecular targets such as SARS-CoV-2 M pro [ 43 ] and neuropilin-1 [ 33 ]. Additionally, a few studies have reported that the potential antiviral effects of phenothiazines may be associated with their ability to inhibit viral binding to plasma membrane receptors [ 44 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, further research is warranted to evaluate more detailed mechanisms of phenothiazines to inhibit the entry of SARS-CoV-2 besides inhibiting CTSL cleavage. Theoretically, phenothiazines as a class of compounds seem not that specific as they were also reported to bind numerous other molecular targets such as SARS-CoV-2 M pro [ 43 ] and neuropilin-1 [ 33 ]. Additionally, a few studies have reported that the potential antiviral effects of phenothiazines may be associated with their ability to inhibit viral binding to plasma membrane receptors [ 44 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a drug-repurposing study several phenothiazine-containing drugs approved by the FDA for the treatment of other medical conditions have been shown to inhibit spike protein-mediated entry of SARS-CoV-2 into cells [Hashizume et al, 2023]. Previous in - silico docking studies identified certain phenothiazines with strong predicted binding to the SARS-CoV-2 M pro active site [Forrestall et al, 2021]. Here, we expand on this concept and demonstrate that some novel phenothiazine urea compounds inhibit both M pro and PL pro or SARS-CoV-2 and have broad antiviral action against other coronaviruses.…”
Section: Introductionmentioning
confidence: 99%